COSMOPOLITIC INDIGENOUS ART in the reverse anthropophagy of Jaider Esbell: na antropofagia reversa de Jaider Esbell - Frade, Isabela; Guimarães, Alexandre (Farol, 2022)
Through the Contemporary Indigenous Art (AIC) concept coined by Jaider Esbell, a macuxi artist, indigenous art establishes itself as a relatively autonomous category in the current scenario, demarcating his leading role framed by the exhaustion of the very concept of art and the severe socio environmental crisis. The text makes an approach to the memory of Jaider Esbell, whose trajectory projects beyond his territory Raposa Serra do Sol, in Roraima, the cosmogonies of the Macuxi people. We revisit, among so many learnings, sown and disseminated in different regions of the country and abroad, its expansion in multiverses. In the rescued ancestral understanding of the macuxi mitic hero Makunaîmî - whose corrected pronunciation, in its countless messages, performances and artistic discursivities, reestablishes a bond with its ancestral meaning through a reverse anthropophagy, proposing a Cosmopolitc Indigenous Art. KEYWORDS: JAIDER ESBELL - COSMOPOLITIC ART - MACUXI COSMOGONY - REVERSE ANTHROPOPHAGY - MAKUNAIMÃ